Do martírio da memória ao encanto da imaginação: uma proposta para formação inicial de professores de História na perspectiva do letramento histórico - Carvalho, Thalia Abreu de (2023)
This research, inserted in the field of Teacher Training and Historical Education, is dedicated to an investigation into the initial training of History teachers from the perspective of the concept of "Historical Literacy". This approach is based on the convergence of two research categories: "Historical Consciousness" and "Historical Literacy". The assumptions of Historical Literacy that are examined here seek to criticize the traditional model of History teaching, promoting alternatives based on a critical view of teaching. The objective of the research is to analyze how the Historical Literacy category contributes to reflection on teaching practices during the initial training of History teachers. The results of this study served as the basis for developing a proposal for initial training for History teachers with a focus on Historical Literacy. To publicize this proposal, the Podcast "PODFORMAR" was created, designed with the purpose of assisting in the training of future teachers who are aware of their role in training critical students and capable of relating school teaching to everyday life.